2017
DOI: 10.1002/chem.201605528
|View full text |Cite
|
Sign up to set email alerts
|

Systematic Study of Open‐Shell Trigonal Pyramidal Transition‐Metal Complexes with a Rigid‐Ligand Scaffold

Abstract: A family of distorted trigonal pyramidal transition-metal complexes [M (N N)Li(THF)] (M=Mn, Fe, Co, Ni) have been studied as candidates for mononuclear single-molecule magnets. Magnetic anisotropy of the family depends on the electronic configuration of the central ion, with the Co analogue exhibiting pronounced SMM behavior.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
14
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 27 publications
(17 citation statements)
references
References 50 publications
1
14
0
2
Order By: Relevance
“…These complexes are expected to lead to large negative D values for d 6,8 and large positive D values for d 7 complexes. Previously, our group has demonstrated that both trigonal monopyramidal23 (TMP) and bipyramidal24 (TBP) geometries can indeed lead to slow magnetic relaxation. These studies also unearthed the fact that very small perturbations in symmetry and metal to metal distances have a distinct effect on magnetic behavior for compounds in the same geometry 24…”
Section: Introductionmentioning
confidence: 99%
“…These complexes are expected to lead to large negative D values for d 6,8 and large positive D values for d 7 complexes. Previously, our group has demonstrated that both trigonal monopyramidal23 (TMP) and bipyramidal24 (TBP) geometries can indeed lead to slow magnetic relaxation. These studies also unearthed the fact that very small perturbations in symmetry and metal to metal distances have a distinct effect on magnetic behavior for compounds in the same geometry 24…”
Section: Introductionmentioning
confidence: 99%
“…Penggunaannya dalam mikroelektronika (19)(20)(21) ditemukan meningkat. NF3 ini merupakan suatu molekul dengan bentuk molekul piramidal trigonal (23)(24)(25)(26) . NF 3 sedikit larut dalam air yaitu 0,021 g/100 ml tanpa mengalami reaksi kimia (235) .…”
Section: Kesimpulanunclassified
“…Penggunaannya dalam mikroelektronika (19)(20)(21) ditemukan meningkat. NF 3 ini merupakan suatu molekul dengan bentuk molekul (22) piramidal trigonal (23)(24)(25)(26) . Pada NF 3 ini terdapat beberapa parameter transfor elektron (10) (Koefisien Townsend (10) , koefisien disosiatif (10) , koefisien fraksi disosiatif (10) , fraksi energi elektron yang hilang akibat tabrakan dengan NF 3 (10) , mobilitas elektron (10) dan kecepatan drift (10) ) gas NF3 ini.…”
Section: Introductionunclassified
“…2,3 This is due to the very high interest in manufacturing reliable single-molecule components for quantum information processing (QIP) applications 4,5 showing quantum phase interference, 6 quantum entanglement of the magnetic states, 7 coherent spin manipulation 8,9 and clock transitions 10 as well as potential hightemperature single-molecule magnetic memory devices. 11 One of the most challenging goals in this vein is the precise design and control of appropriate ligand-scafflods, 12 including the number of donor atoms, their position and symmetry, and the ligand field strength, 13 so that the target SMMs can perform in a completely predictable manner at the highest possible temperature. This led already to significant breakthroughs.…”
Section: Introductionmentioning
confidence: 99%